Mentoring SCA Berbasis Web Madinapay Pada AUMDik Se-Kab. Banyuwangi - Diyah Probowulan; Retno Murwanti (Jurnal Pengabdian Masyarakat Manage, 2024)
Muhammadiyah is a da'wah organization that devotes itself to teaching life based on tawhid and renewal, amar ma'ruf nahi mungkar. Muhammadiyah's education reform aims to unify religion and values and advance the education system. The Council of Education is working hard to improve Amal Usaha Muhammadiyah's (AUM) management in education, especially in the financial management of elementary, junior high, and high school. AUM financial management has improved, but not optimally because AUMDik in Banyuwangi Regency still has not operationalized its financial reporting through the Madinapay website. The results of the current situation analysis of LPPK East Java are (1) LPPK has made efforts to realize effective, efficient and accountable financial governance by creating a budget plan program for Muhammadiyah East Java schools and making financial reporting applications; (2) LPPK has not completed the application with manual guidance; (3) LPPK has carried out system socialization to Muhammadiyah Schools, but the results are not optimal because Muhammadiyah schools in East Java do not use the application until now. The results of service activities at AUMDik in Banyuwangi Regency, especially school treasurers, 1) partners have increased their ability to operate the Madinapay website, 2) some partners already have an integrated financial system but have not been integrated with stakeholders.